The trick is to not get caught up in the expression x-1 view it as a number. If the equation said f(3), then wherever you see the x you replace it with the number 3. So f(3) = (3)^2 -5. Now replace the 3 with x-1.
Let me know if this helps.
Start by getting 2 on the other side.
y'''(t) = 2, take the integral of both sides and you get,
y''(t) = 2t + a. "a" is just a constant. Do the next integral,
y'(t) = t^2 + a*t + b. Take the final integral
y(t) = 1/3*t^3 + a/2*t^2 + b*t +...
There are keywords that can be replaced by mathematical expressions without exception. Let me rewrite the phrase. "the distance to Georgia (Dg) is (=) 1/2 of (*) the distance to Tennessee (Dt)." I am using the variable Dg to be the distance to Georgia and
Dt to be the distance to Tennessee...